Issue Management of the LAZISNU Philanthropic Institution in Strengthening Public Trust in NU-Care Jakarta - Ahmad Soleh; Tria Patrianti; Evi Satispi; Sa'diyah El Adawiyah (PT FORMOSA CENDEKIA GLOBAL, 2026)
NU Care-LAZISNU is one of the largest philanthropic institutions in Indonesia that has a strategic role in collecting and managing zakat, infaq, and alms funds to support education, health, economic, environmental, and da'wah programs. The problem of inconsistency in zakat collection data that appears in the NU Care-LAZISNU report can be understood as part of the organizational communication issue that requires serious handling. The purpose of this study is how the issue management of the philanthropic institution lazisNu strengthens public trust in NU-Care Jakarta. The research method uses a qualitative approach with interviews with 16 selected informants also conducting observations, related documents and triangulation to test the validity of the data. The results of the study show that the issue management implemented by LAZISNU in building and strengthening public trust in NU Care's philanthropic programs is quite good in building and strengthening public trust in the LAZISNU Philanthropic Institution including transparency, negative stigma, and LAZISNU's communication model in managing issues that affect public trust in NU-Care is quite consistent, and the implementation of broader socialization so that it can increase public understanding of the programs run by NU-Care.